Social media addiction and stress as predictors of eating behaviour among undergraduate students: a cross-sectional study - Azmi, Hannah Sorfina; Ibrahim, Muhamad Ariff; Saad, Nurulwahida; Mohd Nazori, Mohd Nazir; Waisulqrnai, Siti Adibah (International Islamic University Malaysia, 2025)
Introduction: The increasing influence of social media and stress on young adults has raised concerns regarding their impact on eating behaviour. University students, in particular, are vulnerable to poor coping strategies that may lead to disordered eating patterns, especially when exposed to high stress and excessive social media use. This study aimed to determine the levels of social media addiction, stress, and eating behaviour among undergraduate students at a Malaysian public university, and to examine their associations and predictive relationships. Methods: A quantitative cross-sectional study was conducted among 383 undergraduate students from all campuses using validated instruments: the Social Media Addiction Scale – Student Form (SMAS-SF), the Perceived Stress Scale (PSS), and the Dutch Eating Behaviour Questionnaire (DEBQ). Results: Correlation analysis showed that stress and social media dimensions such as virtual tolerance, virtual problem, and virtual information were significantly related to at least one type of eating behaviour dimension. Multiple regression analysis showed that stress (β = 0.103, p = 0.048) was a significant predictor of restrained eating. Virtual problem (β = 0.132, p = 0.034) was a significant predictor of emotional eating behaviour. Additionally, virtual tolerance (β = 0.141, p = 0.020), virtual information (β = 0.114, p = 0.042), and stress (β = -0.156, p = 0.002) were significant predictors of external eating behaviour. Conclusion: The study concludes that both social media addiction and stress play a role in shaping students' eating behaviours, with different components influencing restrained, emotional, and external eating in varying directions. These findings suggest the need for varied approaches when addressing unhealthy eating patterns among university students.